Shougang Hierro Peru SAA: labor problem 1993-2010 - Pinto Herrera, Honori (2011)
The work is ubicated in Mining’s sector. It board the labour matter is Shougang Hierro Peru S.A.A. This is the unique company for benefit, to export, to market, to operate and transport the iron from Peru. On the first part there are some theoretical notes in reference to employment and the labour’s problem. The second part contain, essentially, the empirical information with conflict socials happens in San Juan de Marcona, immediately of the conclusions own.